MUTU PENDIDIKAN AGAMA ISLAM DI SEKOLAH DALAM KACAMATA KAMPUS TINJAUAN KURIKULUM, MANAJEMEN, SUPERVISI, DAN HASIL MUTU DI ERA DIGITALISASI SERTA PENGARUHNYA BAGI GENERASI Z - Bukhari Bukhari; Muksinin Muksinin; Ahmad Lahmi; Sri Wahyuni (Ensiklopedia of Journal, 2026)
The quality of Islamic Religious Education (PAI) in schools plays a crucial role in shaping the character and morals of Generation Z (Gen Z), who are growing up in the era of rapid digitalization. This article presents a critical review from an academic perspective on the quality of PAI, focusing on four main aspects: curriculum, management, supervision, and quality outcomes in the school environment. Digitalization offers significant opportunities and challenges, particularly in the relevance of teaching materials, the effectiveness of institutional management, professional supervision of teachers, and the achievement of educational goals. This analysis uses the framework of contemporary Islamic education and management figures to offer rational arguments and proactive solutions so that PAI can produce graduates who are not only digitally proficient but also strong in faith and noble character. The impact of quality PAI on Gen Z is discussed as key to preparing them to become adaptive and responsible agents of change.Keywords: Quality of Islamic Religious Education, Digital Era, Generation Z, Islamic Religious Education Curriculum, Islamic Education Management, Educational Supervision